Catering Theory of Dividend in Dividend Policy: Evidence From Indonesia - Riyanti, Dewi; Yulianto, Arief (Management Analysis Journal, 2018)
This study aims to examine the possibility of companies in paying dividend if there are investors demands for dividends. Researcher used purposive sampling for determine the sample.Sample are used as many as 527 companies with total are 4375 observations during 2007-2016. The data analysis technique used logistic regression in Eviews 9. The results show that investors demands for dividends (catering incentives) were measured by dividend premiums have a positive and significant correlation to dividend payout decisions. It means that companies have bigger probability for paying dividend if the are investors demands. Probability of companies to pay dividend up 2.19 times for increasing a unit of dividend premium.